Social Anxiety and the Generation of Positivity During Dyadic Interaction: Curiosity and Authenticity Are the Keys to Success. Issue 6 (November 2021) - Barber, Kevin C.; Michaelis, Maggie A.M.; Moscovitch, David A.
Highlights: High and low socially anxious participants interacted with low anxious dyads. Social anxiety predicted less positive social outcomes, less positive affect. Affiliative social goals predicted more positive social and affective outcomes. Curiosity and authenticity mediated relations between affiliation and outcomes. Dyadic analyses enabled disentangling of participant and partner effects. Abstract: What drives positive affective and interpersonal experiences during social interaction? Undergraduates with high ( n = 63) or low ( n = 56) trait social anxiety (SA) were paired with unfamiliar low SA partners in a 45-minute conversation task. Throughout the task, participants and their conversation partners completed measures of affiliative goals, affect, curiosity, authenticity, and attentional focus. Both affective and interpersonal outcomes were assessed. Dyadic analyses revealed that participants' affiliative goals during the social interaction predicted positive outcomes for both themselves and their partners, although the link between affiliative goals and positive affect was weaker for participants with high SA. Mediation analyses demonstrated that adopting affiliative goals may promote more positive outcomes by increasing participants' curiosity and felt authenticity. Taken together, results illuminate the pathways through which people with varying levels of trait SA may derive interpersonally generated positive affect and positive social outcomes, with implications for clinical theory and practice.